2007
DOI: 10.1007/s00268-007-9235-8
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of High‐output Enterocutaneous Fistulas with a Vacuum‐compaction Device. A Ten‐year Experience

Abstract: The vacuum-compaction device proved effective for reducing fistula output in 89 of 91 patients (97.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…Approximately, one-third of enterocutaneous fistulae will close spontaneously with proper supportive care, control of sepsis, and nutritional support [30]. Wainstein et al [31] reported that fistulae healed spontaneously in 46 % of patients, within a mean period of 90 days (range 8–370 days). Peng et al [32] reported that irrigation-suction through the drainage tubes was effective in approximately 75 % of patients with leakage, without the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, one-third of enterocutaneous fistulae will close spontaneously with proper supportive care, control of sepsis, and nutritional support [30]. Wainstein et al [31] reported that fistulae healed spontaneously in 46 % of patients, within a mean period of 90 days (range 8–370 days). Peng et al [32] reported that irrigation-suction through the drainage tubes was effective in approximately 75 % of patients with leakage, without the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, management of bowel fistulae revolves around nutrition, diversion or reoperation, and treatment of sepsis. [6970]…”
Section: Discussionmentioning
confidence: 99%
“…Advances in parenteral nutrition (PN), radiological diagnosis, and treatment of intraabdominal abscesses and antibiotics among others have led to a decrease in mortality rates which were previously reported at ∼40% to the current ∼10%. [1][2][3] When initially diagnosed most patients already suffer at least one of the frequent complications related to ECF such as sepsis, malnutrition, and fluid and electrolyte imbalance; these are the main causes of morbidity and mortality. Medical therapy aims to treat these complications and favor spontaneous closure.…”
Section: Introductionmentioning
confidence: 99%